The Fatty Acid Composition and Properties of Oil Extracted from Seeds of Carum roxburghianum Benth. (Radhuni) - Paul, BK; Ahmed, MN; Saha, GC (Bangladesh Journal of Scientific and Industrial Research, 2011)
Carum roxburghianum Benth. (Radhuni) seeds of three different places of Bangladesh were investigated to determine the fatty acid composition and physico-chemical properties of extracted oil. The seeds were found to contain oil ranging from 15.31 to 20.32%. The percentage compositions of fatty acids were identified and quantified by Gas Liquid Chromatography (GLC). The saturated and unsaturated fatty acids in extracts were 4.95 to 6.27% and 93.73 to 94.89%, respectively. Among six fatty acids identified in this study, oleic acid contributed the highest portion (76.44 to 79.16%), whereas, linoleic (1.38%), linolenic (15.28 - 15.40%), stearic (0.70%), palmitic (4.95 - 5.57%) and ecosenoic acid (0.51 - 15.73%) together contributed the rest. Physico-chemical properties of the oil extracted were also investigated. The specific gravity, refractive index, optical rotation were recorded as 0.903 to 0.918 at 30°C, 1.465 to 1.470 at 30°C and +8.54° to +9.56° at 26°C, respectively. The chemical properties like saponification value (183.52 - 193.45), iodine value (80.99 - 120.90), peroxide value (23.25 - 36.16), acid value (143.84 - 162.99), ester value (48.12 - 62.03), percentage of unsaponifiable matter (3.56 - 6.51%), Reicher-Meissel value (2.00 - 3.12), Polenske value (4.12 - 6.20) and Henher value (85.12 - 95.56) were determined. Overall Radhuni seeds oil can be considered as a good source of oleic acid. Keywords: Carum roxburghianum; Radhuni seed oil; fatty acid composition; oleic acid; Gas Liquid Chromatography. DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8113 Bangladesh J. Sci. Ind. Res. 46(1), 111-116, 2011